The Effectiveness and Distribution of Fishing Light Attractors on the Stationary Lift Net - fuad, Fuad; Primyastanto, Mimit; Pranowo, Doddy; Maulana, Eka; Sari, Wahida Kartika; Surpiyadi, Supriyadi (Research Journal of Life Science, 2022)
A stationary lift net requires an effective fishing light attractor. The intensity and distribution of light are important factors to increase the effectiveness of fishing light attractors. This study aimed to probe the distribution of light intensity and its effect on the effectiveness of fishing light attractors. This research employed a descriptive-comparative method by comparing the effectiveness of LED lights with kerosene lights. The results showed that the concentration of fish school in LED lights was at a depth of 4–10 m with a light intensity of 1x10-8– 10x10-8W/cm2, while the kerosene lights was deeper than LED lights at a depth of 8–12 meters with a light intensity of 1x10-8– 10x10-8W/cm2. The distribution of fish schools from LED lights tends to be concentrated and form larger schools than kerosene lights. The optimum light intensity of LED and kerosene lights was almost the same, in the range of 1x10-8– 10x10-8W/cm2, with concentrations of fish schools reaching 65% and 64%, respectively. The total catch of LED lights fish during eight fishing trips was 168.5 kg or an average of 21.06±2.32 kg/trip, while the total catch of kerosene lights was 139.6 or an average of 17.5±1.98 kg/trip.